2020
DOI: 10.1002/jimd.12268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of higher and more frequent dosing of alglucosidase alfa and immunomodulation on long‐term clinical outcome of classic infantile Pompe patients

Abstract: The aim of this study was to compare the long-term outcome of classic infantile Pompe patients treated with 20 mg/kg alglucosidase alfa every other week (eow) to those treated with 40 mg/kg/week, and to study the additional effect of immunomodulation. Six patients received 20 mg/kg eow and twelve 40 mg/ kg/week. Five patients were cross-reactive immunologic material (CRIM)-negative, two in the 20 mg, three in the 40 mg group. We compared (ventilatorfree) survival, motor outcome, infusion associated reactions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
(120 reference statements)
1
26
0
Order By: Relevance
“…The proportion of patients with a (very) high peak titer in our study is comparable to what we previously reported in adult patients (23% vs. 22%) [ 14 ]. We found high sustained antibody titers in only one patient (with short follow up duration), which is also comparable to adults, but in contrast to what is reported in classic infantile Pompe disease patients, especially in CRIM negative patients [ 13 , 22 ]. We postulated that lower endogenous α-glucosidase activity may lead to higher antibody titers, which was previously hypothesized in adults too [ 14 ].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The proportion of patients with a (very) high peak titer in our study is comparable to what we previously reported in adult patients (23% vs. 22%) [ 14 ]. We found high sustained antibody titers in only one patient (with short follow up duration), which is also comparable to adults, but in contrast to what is reported in classic infantile Pompe disease patients, especially in CRIM negative patients [ 13 , 22 ]. We postulated that lower endogenous α-glucosidase activity may lead to higher antibody titers, which was previously hypothesized in adults too [ 14 ].…”
Section: Discussionsupporting
confidence: 60%
“…Patient 1 was only 1 year old when ERT was started, therefore assessment of the MRC, QMFT and FVC could not be performed during the first years of treatment. The motor domain of the Bayley Scales of Infant Development-II (BSID-II), which is a tool for developmental assessment in the first 2 years of life, showed a delayed motor development at start of ERT (BSID-II SD score < − 3.0) [ 22 ]. During the first 2 years of treatment, the BSID-II improved to SD scores between − 1.7 and − 0.6, which are age-equivalent scores, reflecting normal development (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ERT may be started in patients with typical cardiorespiratory symptoms if the enzyme is deficient in DBS, even before seeing the genetic result ( 52 ). The usual recommended dose is 20 mg/kg alglucosidase alfa every other week; however, a recent study showed that patients treated with higher doses and more frequent injections had a better outcome such as motor, respiratory, and biochemical markers ( 53 , 54 ).…”
Section: Treatmentmentioning
confidence: 99%